Coping with crisis: government reactions to the great recession (New York, 2012)
"The financial crisis that erupted on Wall Street in 2008 quickly cascaded throughout much of the advanced industrial world. Facing the specter of another Great Depression, policymakers across the globe responded in sharply different ways to avert an economic collapse. Why did the response to the crisis—and its impact on individual countries—vary so greatly among interdependent economies? How did political factors like public opinion and domestic interest groups shape policymaking in this moment of economic distress? Coping with Crisis offers a rigorous analysis of the choices societies made as a devastating global economic crisis unfolded."